1992
DOI: 10.1111/j.1439-0418.1992.tb00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐associated biotypes within West African populations of the whitefly Bemisia tabaci (Genn.), (Hom., Aleyrodidae)

Abstract: Host-associated differences within populations of the whitefly Bemzsiu tabucz from cassava, okra and other host plants in C6te d'Ivoire, West Africa, were investigated by iso-enzyme electrophoresis and experimental host range studies. Two biotypes were identified. One was found only on cassava and eggplant; the other was polyphagous, but did not infest cassava. Differences in esterase patterns matched these host range restrictions exactly. The implications of these finding are discussed in relation to the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 11 publications
13
123
0
2
Order By: Relevance
“…Burban et al [104] first showed host-associated differences among populations of B. tabaci from cassava and okra and other host plants in Côte d'Ivoire, based on isozyme electrophoresis and experimental host range studies. This report was corroborated by the presence of cassava and non-cassava haplotypes based on RAPD-PCR markers and the internal transcribed spacer-1 (ITS-1) [105].…”
Section: Whitefly B Tabaci Vector: Biological and Genetic Variabilitymentioning
confidence: 99%
“…Burban et al [104] first showed host-associated differences among populations of B. tabaci from cassava and okra and other host plants in Côte d'Ivoire, based on isozyme electrophoresis and experimental host range studies. This report was corroborated by the presence of cassava and non-cassava haplotypes based on RAPD-PCR markers and the internal transcribed spacer-1 (ITS-1) [105].…”
Section: Whitefly B Tabaci Vector: Biological and Genetic Variabilitymentioning
confidence: 99%
“…담배가루이(Bemisia tabaci)는 전 세계적으로 발생하며, 600여종 이상의 기주를 가해하는 주요 흡즙성 해충으로 (Perring, 2001), 기주 선호성이나 매개하는 바이러스 등 에 따라 24종의 생태형이 보고되어 있다 (Bedford et al, 1994;Burban et al, 1992). 담배가루이는 식물의 체관부 를 흡즙하여 직접적인 피해를 주거나 간접적으로 감로배설 로 인한 그을음병을 유발하고 100종 이상의 바이러스를 매 개하는 등 시설재배 작물의 상품성과 수량에 영향을 준다 (Byrne, 1999;Bedford et al, 1994;Jones, 2003) (Choi, 1990;Devine and Denholm, 1998;Nauen et al, 2002).…”
Section: 서 론unclassified
“…It was primarily divided in to B biotype, Q biotype and non B/Q biotype. The non B/Q biotypes includes more than 20 biotypes such as A, K, D, E, G, H, L, M, N [12] . The taxonomy of the whitefly is based on the morphological characteristics of the fourth nymphal stage (pupal case) [13] .…”
Section: Introductionmentioning
confidence: 99%